Atomic structure, diffusivity and viscosity of Al1-xMgx melts from ab initio molecular dynamics simulations (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Diffusivity and viscosity of Al1-xMgx (x=0, 0.0039, 0.12, 0.92, 0.9961, 1）melts at 875K, 1000K, 1125K, and 1250K were investigated by the ab initio molecular dynamics (AIMD) approach. The simulated results are compared with available experimental and calculated data in literature and reasonable agreements are obtained. Considering the results of g(r), it can be observed that Mg atoms in Al0.88Mg0.12 melt aggregate more obviously at 1000K and 1250K. For Al0.08Mg0.92, Al atom segregation is more obvious at 875K and 1000K. The tracer diffusion coefficients of Al or Mg in Al1-xMgx (x=0.12, 0.92) melts, and interdiffusion coefficients of Al0.88Mg0.12 and Al0.08Mg0.92 melts are all close to the self-diffusion coefficients of Al or Mg. With the increasing temperature, the diffusivity increases linearly. In dilute melts, the tracer diffusion coefficients of solute atom and the interdiffusion coefficients increase nonlinearly with the increasing temperature. For Al0.88Mg0.12 and Al0.88Mg0.12 melts, the viscosities η are comparatively higher than pure melts. The viscosities of all melts show the same tendencies, which decrease with the increasing temperature, then increase at 1250K. The results obtained in the present work provide an insight into the design of Al and Mg alloys.
Keywords: Al1-xMgx melt; AIMD; Diffusivity; Viscosity